Theoretical approaches to the study of the subjective well-being phenomenon - Sergey A. Vorozheikin (Saratov State University, 2022)
The necessity to "reconcile" various research positions regarding the study of subjective well-being phenomenon on the basis of an integrated approach makes the study of the theoretical approaches to the phenomenon relevant. Despite the abundance of modern scientific publications in the field of psychology devoted to the study of well-being, there is a lack of a unified understanding of the nature of this phenomenon. Scientists use a lot of concepts that are similar in content, but are not strictly differentiated. A new research agenda, based on positive psychology, offers a different look at the subjective well-being phenomenon considering it as a synonym for happiness. This has a great research and practical value. The current direction in the study of the subjective well-being phenomenon is not limited to the analysis of the factors influencing it, but it also comprises their combination and interaction, which requires a fundamentally different approach to further research. The objective of the study is to analyze the main theoretical approaches of Russian and foreign researchers to the study of the issues related to the subjective well-being phenomenon. The researcher has determined the prospects of empirical study of the subjective well-being that will be based on the results of the current studies of the personality determinants, such as the type of self-regulation, emotional intelligence, social skills of the subject, control locus, etc. An objective picture of their correlation will help in the development of a program of controlled socialization of the personality. Such program would guarantee the achievement of a person's subjective well-being, as well as contribute to fulfilling the psychotherapeutic function of achieving subjective well-being.